Principles of nucleic acid structure - Neidle, Stephen; Sanderson, Mark (Academic Press, 2021)
Principles of Nucleic Acid Structure, Second Edition, provides the most complete and concise summary of underlying principles and approaches to studying nucleic acid structure, including discussions of X-ray crystallography, NMR, molecular modelling and databases. The book's focus is on a survey of structures that are especially important for biomedical research and pharmacological applications. This updated edition includes the latest advances relevant to recognition of DNA and RNA by small molecules and proteins, including sections on RNA folding, ribosome structure and antibiotic interactions, DNA quadruplexes, DNA and RNA protein complexes and short interfering RNA (siRNA). This reference is a must-have for those seeking an authoritative, comprehensive and up-to-date source on all aspects of nucleic acid structure, from basic first principles to details of recent research results.